UJI EKSTRAK BAWANG BOMBAY TERHADAP ANTI BAKTERI GRAM NEGATIF Pseudomonas aeruginosa DENGAN METODE DIFUSI CAKRAM - Wuryanti, Wuryanti; Murnah, Murnah (JURNAL SAINS DAN MATEMATIKA, 2009)
ABSTRACT—Microbe is a microscopic living organism which is closely linked to human life. One of patogenic microorganisms such as Pseudomonas aeruginosa may cause diseases. Sulfure of several plants are bioactive as antimicrobial. The properties of sulfure in Allium cepa L leads to an assumption that it has antimicrobial properties. Therefore, this study involved the antimicrobial test. The determination steps of antimicrobial Allium cepa L extract consisted of the Allium cepa L extract preparation, microbial regeneration and antimicrobial test. The antibacterial determination were performed by paper disk method. Based on the research data, determination of antimicrobial white Allium cepa L extract resulted in inhibition zone area showed that the extract owned antimicrobial property. Key words : Allium cepa L, sulfure, Pseudomonas aeruginosa